Establishment Of A Zebrafish Embryonic Stem Cell Line Using A Feeder-Free Culture Method And In Vitro Pluripotency Characterization - Ho, Sing Yee (2014)

(untitled)
Feeder layers are commonly used in zebrafish embryonic stem (ES) cell cultures to enable proliferation and prevent differentiation of the ES cells. In this study, a culture method using feeder-free was employed to derive and establish longterm zebrafish ES cell line from zebrafish blastula stage embryos. Lapisan sel penyuap telah biasa digunakan dalam kultur sel tunjang embrionik daripada ikan zebra untuk membolehkan proliferasi dan mencegah pembezaan sel-sel tersebut. Dalam kajian ini, kaedah kultur tanpa lapisan sel penyuap telah diguna untuk menghasilkan titisan sel tunjang embrionik jangka masa panjang daripada embrio peringkat blastula ikan zebra.